Measuring access to Kidney transplantation - Lima, Bruno A. (2014)
Kidney allocation from cadaveric donors must balance two main principles: medical utility and justice. The principle of medical benefit is gauged by maximizing efficiency in the use of organs, and the principle of justice by its effectiveness ensuring that all patients have a reasonable opportunity to be transplanted. The survival benefit of transplant patients when compared with dialyzed values is well described even after adjusting for age, comorbidities, albumin and Body Mass Index (BMI). This benefit is also observed in patients over the age of 60 years. Several factors are related to transplant efficiency: maximization of HLA matching for patients that are more relevant (children and youth), preference for children; minimization of ischemia time, and the relation of life expectancy of the graft with life expectancy of the receptor. The factors related to justice are: reduction of waiting times, and greater equity of access for patients regardless of their race, blood group, HLA homozygosity and geographic location. There are socio-demographic and immunological factors associated with longer waiting time for kidney transplantation, such as: age, blood group or sensitization against HLA antibodies.Knowing the prevalence and incidence (per year, per million inhabitants) of kidney transplant candidates’ demographic factors such as: sex, age groups, socioeconomic status, clinical and immunological characteristics: blood group, PRA values, BMI, type of dialysis, cause of renal failure, and comorbidities; allows for an objective comparison of allocation programs. The waiting time for transplantation should be measured as the median time between the start of dialysis and transplantation of wait listed patients each year. By using the Cox regression analysis, with time on dialysis to transplantation as a dependent variable and clinical and socio-demographic factors as independent variables, will shed light on which characteristics most affect the access to transplantation. Only by defining and applying standardized metrics to kidney transplant candidates over time, is it possible to make informed decisions when debating organ allocation rules. “What gets measured gets improved”.